2005
DOI: 10.1152/ajpheart.00400.2005
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane induces second window of preconditioning through upregulation of inducible nitric oxide synthase in rat heart

Abstract: The second window of preconditioning (SWOP) induced by inhalation of volatile anesthetics has been documented in the rat heart and is triggered by nitric oxide synthase (NOS), but involvement of NOS in the mediator phase of isoflurane-induced SWOP has not been demonstrated. We tested the hypothesis that isoflurane-induced SWOP is mediated through upregulation of inducible NOS (iNOS). Rats inhaled 0.75 minimum alveolar concentration (MAC) isoflurane, 1.5 MAC isoflurane, or O2 for 2 h. After 24, 48, 72, and 96 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 35 publications
2
35
1
Order By: Relevance
“…anesthetics can induce the cardioprotective effect of both preconditioning (6,18,19,24,27) and postconditioning (4,8,28). Because the primary end point of the present study was the assessment of cardioprotection, we felt it was important to avoid the confounding factors that are associated with anesthetics and open-chest animal models.…”
Section: Discussionmentioning
confidence: 99%
“…anesthetics can induce the cardioprotective effect of both preconditioning (6,18,19,24,27) and postconditioning (4,8,28). Because the primary end point of the present study was the assessment of cardioprotection, we felt it was important to avoid the confounding factors that are associated with anesthetics and open-chest animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Chiari et al (2005) demonstrated in rabbits that nitric oxide (NO) derived from endothelial NO synthase (eNOS), but not from inducible NO synthase (iNOS), plays a role in both triggering and mediating isoflurane-induced late PC against myocardial infarction, whereas Wakeno-Takahashi et al (2005) found in rats that overexpression and activation of iNOS was critical. The involvement of NO, and the relative roles of eNOS and iNOS, in the late anti-stunning effect of isoflurane remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Postischemic left ventricular function in the rat heart was improved and iNOS expression and activity in the heart were increased after the inhalation of isofl urane; also, a selective iNOS inhibitor, 1400 W, abolished iNOS activation and cardioprotection [21]. Isofl urane appears to induce a second window of preconditioning through the overexpression and activation of iNOS in the heart.…”
Section: Ischemia and Anesthetic Preconditioningmentioning
confidence: 89%